The Resource: of Efforts to Improve Business Through Technology as a Media For Promotion of Bamboo Woven Crafts - fajrin, Siti Fadilah Fajrin (TRIDAYA: Jurnal Pengabdian kepada Masyarakat, 2024)
In this era of modernization, the existence of woven bamboo crafts is declining. Many aspects are factors in this decline in existence. One of them is the lack of product marketing, so it is difficult for people to get information about woven bamboo handicraft products.